Self-Compassion Among Youth with Child Maltreatment Histories and Psychological Distress: A Scoping Review - Wong, Nikki; Kim, Katherine; Ren, Peri (Pei Rui); Liu, Wai Sun; Oh, Sehyun Shannon; Strickland, Noelle; Stewart, Sherry H.; Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objective: Focusing on youth (ages 15-24), our scoping review aims to address these questions: (1) What is the relationship between self-compassion (SC) and psychological distress in youths with child maltreatment (CM) histories? and (2) How does this relationship differ across child maltreatment types? Methods: Eight databases were screened: OVID MEDLINE, OVID PsychInfo, PsycARTICLES, ProQuest Sociological Abstracts, ProQuest ERIC, OVID Embase, CINAHL, and PUBMED. Our search strategy and inclusion/exclusion criteria yielded an initial 4143 studies. With 1365 duplicates removed, 2778 titles and abstracts were screened. 17 studies were included for full-text screening, and seven studies were selected for data extraction and final inclusion. Results: SC was found to moderate and mediate the relationships between CM and psychological distress. The role of fear of SC was also investigated and found to function as a mediator between CM and PTSD symptom severity. Regarding CM types, emotional abuse was found to significantly predict SC levels in a child welfare population. Implications: Given the significance of SC and fear of SC in the relationship between CM and psychological distress, implementation of SC into clinical practice should be considered. Recommendations are made to expand research into more diverse populations, such as child welfare and/or Indigenous youth.